Genotype-Phenotype Correlations for Pathogenic COL4A3–COL4A5 Variants in X-Linked, Autosomal Recessive, and Autosomal Dominant Alport Syndrome - Savige, Judy; Huang, Mary; Croos Dabrera, Marina Shenelli; Shukla, Krushnam; Gibson, Joel (Frontiers in Medicine, 2022)
Alport syndrome is inherited as an X-linked (XL), autosomal recessive (AR), or autosomal dominant (AD) disease, where pathogenic COL4A3 – COL4A5 variants affect the basement membrane collagen IV α3α4α5 network. About 50% of pathogenic variants in each gene (major rearrangements and large deletions in 15%, truncating variants in 20%, splicing changes in 15%) are associated with “severe” disease with earlier onset kidney failure, and hearing loss and ocular abnormalities in males with XL inheritance and in males and females with AR disease. Severe variants are also associated with early proteinuria which is itself a risk factor for kidney failure. The other half of pathogenic variants are missense changes which are mainly Gly substitutions. These are generally associated with later onset kidney failure, hearing loss, and less often with major ocular abnormalities. Further determinants of severity for missense variants for XL disease in males, and in AD disease, include Gly versus non-Gly substitutions; increased distance from a non-collagenous interruption or terminus; and Gly substitutions with a more (Arg, Glu, Asp, Val, and Trp) or less disruptive (Ala, Ser, and Cys) residue. Understanding genotype-phenotype correlations in Alport syndrome is important because they help predict the likely age at kidney failure, and the need for early and aggressive management with renin-angiotensin system blockade and other therapies. Genotype-phenotype correlations also help standardize patients with Alport syndrome undergoing trials of clinical treatment. It is unclear whether severe variants predispose more often to kidney cysts or coincidental IgA glomerulonephritis which are recognized increasingly in COL4A3-, COL4A4 - and COL4A5-associated disease.